2017
DOI: 10.3390/educsci7040086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chemistry Student Teachers’ Diagnostic Competence—A Qualitative Cross-Level Study

Abstract: Diagnostic competence is an important skill of professional teachers and is a part of Pedagogical Content Knowledge (PCK). Because increasing heterogeneity and diversity characterize our schools, diagnostic competence plays a prominent role in teacher pre-and in-service courses. At our university, two modules are focused on examining student teachers' diagnostic competence in chemistry. The present paper describes a cross-level case study analyzing three groups of student teachers in different phases of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
2
7
0
2
Order By: Relevance
“…Both countries assumed success in sensitizing chemistry student teachers to heterogeneity and diversity in chemistry classes, what is recognizable in the reactions of the student teachers in the courses. Similar results about the sensitizing and awareness of pedagogical diagnosis also evident in the parallel (and broader) studies during the development process in Germany (see Tolsdorf & Markic, 2017;Tolsdorf & Markic, in review) and in Finland based on the preliminary results of the present study. Already Haq and Mundia (2012) reported that the individual dimensions must be experienced during the teacher training program.…”
Section: Discussion Conclusion and Future Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…Both countries assumed success in sensitizing chemistry student teachers to heterogeneity and diversity in chemistry classes, what is recognizable in the reactions of the student teachers in the courses. Similar results about the sensitizing and awareness of pedagogical diagnosis also evident in the parallel (and broader) studies during the development process in Germany (see Tolsdorf & Markic, 2017;Tolsdorf & Markic, in review) and in Finland based on the preliminary results of the present study. Already Haq and Mundia (2012) reported that the individual dimensions must be experienced during the teacher training program.…”
Section: Discussion Conclusion and Future Implicationssupporting
confidence: 90%
“…Examples taken from actual practice are also given to support student teachers' understanding. Before the module (ChemEd 2) starts, the student teachers have almost no knowledge about diagnostic instruments (Tolsdorf & Markic, 2017). For this purpose, we have developed a learning-at-stations module where the different instruments are presented.…”
Section: Methods For Learning About Different Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transforming this idea into the teaching of mathematics, teacher's diagnostic competence could be defined as teachers' ability to interpret students' thinking and reasoning process, to monitor students' progress and difficulties, and to provide appropriate responses to the results of the diagnosis. With respect to diagnostic competence, students have different preconditions therefore teachers need to recognize each student (Tolsdorf & Markic, 2017) and must be able to describe and interpret the individual student's abilities and difficulties.…”
mentioning
confidence: 99%
“…The development needs to be started during the university teacher training program, but very few studies investigate the development of diagnostic competence in the chemistry teachers training program. Tolsdorf and Markic (2017) showed in their cross-level study that student teachers` diagnostic competence differs at different stages of their teacher training program. It is also to see that courses and internship influence their development in different ways.…”
Section: / 13mentioning
confidence: 99%